Single-center real-world data and technical considerations from 100 consecutive patients treated with the Perceval aortic bioprosthesis - Müller, Hannes; Szalkiewicz, Philipp; Benedikt, Peter; Ratschiller, Thomas; Schachner, Bruno; Schröckenstein, Sophie; Zierer, Andreas (Frontiers in Cardiovascular Medicine, 2024)
Objectives Although the Perceval sutureless aortic valve bioprosthesis presents a feasible alternative to conventional aortic valve prostheses, the extent of its applicability with respect to technical considerations for a real-world patient collective is still under debate. Methods One hundred patients received the Perceval prosthesis [males: 59; age: 72.5 (7.3–79) years] between December 2015 and February 2023 [EuroSCORE II: 2.8 (1.7–5.4)] for an aortic valve replacement (AVR), with additional concomitant procedures, for underlying severe aortic valve stenosis [n = 93 (93)], endocarditis [n = 5 (5)], and redo AVR [n = 7 (7)] including a prior surgical AVR [n = 4 (4)] and a failed transcatheter aortic valve implantation [n = 3 (3)]. Surgery was conducted primarily by median sternotomy [n = 71 (71)] and, alternatively, by the upper hemisternotomy approach [n = 29 (29)]. Results Over a median follow-up time of 36.5 (16.5–53) months, eight patients (8%) underwent postoperative pacemaker implantation, with five (5%) due to high-grade atrioventricular block, while nine patients experienced a stroke (9%). The median values of maximum and mean gradients across all valve sizes were 22 (18–27.5) mmHg and 10 (13–18) mmHg, respectively. Two patients (2%) had moderate and one (1%) had severe paravalvular leakage, with the latter presenting the only case of underlying valve migration and induced redo AVR with valve explantation 2 days following initial surgery. Thirty-day mortality (and overall mortality) was 5% and 26%, respectively. Conclusion The implantation of the Perceval bioprosthesis is feasible for a variety of indications, with excellent hemodynamic results and low complication rates in a real-world high-risk patient collective.